Electromagnetic shielding material and preparation method and application thereof

By immersing the cotton fabric in a saturated NaOH solution of divalent copper salt and carbonized, a copper elemental carbonaceous material with high efficiency electromagnetic shielding performance is obtained, which solves the problems of complex process and limited performance in the prior art, and realizes the realization of Simple and efficient electromagnetic shielding effect.

CN119136525APending Publication Date: 2024-12-13SHAANXI UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411271703.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2024-12-13

Smart Images

  • Figure CN119136525A_ABST
    Figure CN119136525A_ABST
Patent Text Reader

Abstract

The invention discloses an electromagnetic shielding material and a preparation method and application thereof.The preparation method comprises the steps that firstly, a cotton fabric is placed in a saturated NaOH solution of bivalent copper salt to be subjected to an impregnation reaction, and a modified cotton fabric is prepared; and washing and drying the modified cotton fabric, and carbonizing to obtain the electromagnetic shielding material. The method is simple in process and reasonable in design, the electromagnetic shielding material with excellent performance can be obtained only through simple dipping and carbonization treatment, the method is suitable for industrial expanded application, and meanwhile the product has good electromagnetic shielding effectiveness based on the copper elementary substance and the carbonaceous material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electromagnetic shielding material development, and relates to an electromagnetic shielding material and a preparation method and application thereof. Background Art

[0002] In recent years, electronic information technology has developed rapidly, bringing great convenience to people's lives, but a large amount of electromagnetic waves has also had a huge impact on human survival and development, namely electromagnetic interference. The electromagnetic waves generated during the operation of electronic equipment can cause electronic equipment to degrade or even malfunction, thereby restricting the development of the electronics industry, causing important information to be leaked, and even endangering commercial and national security. Most importantly, modern medicine has proven that long-term electromagnetic radiation can affect human health, and electromagnetic radiation energy can be transmitted to cells, causing abnormal body temperature and protein inactivation. In addition, electromagnetic waves increase the possibility of gene mutations, and the long-term effects of a large amount of electromagnetic waves may cause serious health problems, including dizziness, sleep disorders, and increased incidence of teratomas and cancer.

[0003] Developing electromagnetic shielding composite materials is the main way to shield electromagnetic waves. Traditional metal electromagnetic shielding materials, such as aluminum foil and copper mesh, have high electromagnetic shielding effectiveness. However, pure aluminum foil or copper mesh is easy to oxidize, corrode, and have limited electromagnetic shielding effectiveness. At the same time, the current shielding is mainly based on reflection. After reflection, only a small amount of electromagnetic waves enter the metal-based material, and a large amount of electromagnetic waves are repeatedly reflected, which eventually leads to severe attenuation of electromagnetic waves and achieves the shielding effect. However, reflection will cause secondary pollution of electromagnetic waves. In addition, in addition to aluminum foil and copper mesh, the materials used for electromagnetic shielding are mainly graphene, MXene, metallic silver, and polymer materials. These materials show good shielding performance, but there are problems such as high price, complex preparation process, and difficulty in large-scale synthesis. Summary of the invention

[0004] In view of the problems existing in the prior art, the present invention provides an electromagnetic shielding material and a preparation method and application thereof, thereby solving the technical problems in the prior art that the preparation process of electromagnetic shielding materials is complex, it is difficult to synthesize in large quantities, and the shielding performance is limited.

[0005] The present invention is achieved through the following technical solutions:

[0006] A method for preparing an electromagnetic shielding material comprises the following steps:

[0007] S1: placing cotton fabric in a saturated NaOH solution of divalent copper salt for immersion reaction to obtain modified cotton fabric;

[0008] S2: After washing and drying the modified cotton fabric, carbonization treatment is performed to obtain the electromagnetic shielding material.

[0009] Preferably, the saturated NaOH solution of the divalent copper salt is prepared by placing copper oxide or a divalent copper salt in an excess of sodium hydroxide solution and allowing it to react.

[0010] Preferably, the concentration of the sodium hydroxide solution is 5wt% to 10wt%.

[0011] Preferably, the copper oxide or divalent copper salt is allowed to react in a sodium hydroxide solution for 24 to 48 hours.

[0012] Preferably, in step S1, the cotton fabric is immersed in a saturated NaOH solution of a divalent copper salt for 48 to 72 hours.

[0013] Preferably, in step S2, the drying temperature is 50-70° C., and the drying time is 8-12 hours.

[0014] Preferably, in step S2, the carbonization treatment is performed under an argon atmosphere.

[0015] Preferably, in step S2, during the carbonization treatment, the heating rate is 5°C / min, the holding temperature is 700-900°C, the holding time is 1-2h, the cooling rate is 2°C / min, and the temperature is cooled to 200°C and then naturally cooled to room temperature.

[0016] An electromagnetic shielding material is prepared by the above method.

[0017] Application of the above-mentioned electromagnetic shielding material in electronic equipment.

[0018] Compared with the prior art, the present invention has the following beneficial technical effects:

[0019] The invention discloses a method for preparing an electromagnetic shielding material. Firstly, a cotton fabric is placed in a saturated NaOH solution of a divalent copper salt for an impregnation reaction. This step is the key to the modification. The divalent copper salt reacts in the NaOH solution to generate sodium tetrahydroxycuprate. The copper ions in the sodium tetrahydroxycuprate react with the hydroxyl groups on the cotton fabric fibers to form coordination bonds. This coordination effect makes the copper ions firmly fixed on the cotton fibers. In addition, the cotton fiber molecules contain a large number of hydroxyl groups, which can form hydrogen bonds with the hydroxyl groups or water molecules in the sodium tetrahydroxy cuprate molecules, effectively enhancing the binding force between the two. At the same time, combined with the electrostatic adsorption and van der Waals force between sodium tetrahydroxy cuprate and cotton fabric fibers, the binding force between sodium tetrahydroxy cuprate and cotton fabric is effectively improved. The modified cotton fabric is then washed and dried, and then carbonized. The purpose of washing and drying is to remove excess divalent copper salts and NaOH, as well as other by-products, to ensure the purity of the modified cotton fabric. During the carbonization process, organic components such as cellulose in the cotton fabric will undergo pyrolysis to form carbonaceous materials. At the same time, the copper ions in the sodium tetrahydroxy cuprate are reduced to copper elements attached to the surface of the formed carbonaceous materials. In the electromagnetic field, copper elements can quickly convert the electric field components in the electromagnetic wave into current and conduct it through the inside of the material. This efficient current conduction can significantly attenuate the energy of the electromagnetic wave, thereby achieving the effect of electromagnetic shielding. The porous structure and good conductivity of carbonaceous materials also scatter and absorb electromagnetic waves, thereby further enhancing the electromagnetic shielding performance of the entire material. The electromagnetic waves are repeatedly reflected and absorbed between the carbonaceous base material and the copper element, effectively improving the electromagnetic shielding performance of the material. This method has a simple process and a reasonable design. An electromagnetic shielding material with excellent performance can be obtained through simple impregnation and carbonization treatment. It is suitable for industrial expansion and application. At the same time, the product has good electromagnetic shielding effectiveness based on copper element and carbonaceous materials.

[0020] Further, the saturated NaOH solution of the divalent cupric salt is prepared by placing copper oxide or divalent cupric salt in an excess of sodium hydroxide solution and allowing the reaction to proceed. First, due to the use of an excess of sodium hydroxide solution, it is possible to ensure that copper oxide or divalent cupric salt is completely dissolved and converted into the desired sodium tetrahydroxycopperate, and this excess condition helps to overcome the limitations in the reaction kinetics and makes the reaction more thorough. By adding an excess of sodium hydroxide at one time and allowing the reaction to proceed, the steps of adding and adjusting the concentration of the solution for multiple times can be omitted, thereby simplifying the preparation process and improving production efficiency. In addition, excess sodium hydroxide helps to suppress the generation of other by-products, such as the precipitation of copper hydroxide, etc., which helps to maintain the purity of the solution and reduce the burden of removing by-products in subsequent treatment. This process can make the uniform distribution of copper ions help to form a continuous conductive network, thereby improving the current conduction efficiency of the material, and the firm combination helps to prevent the copper ions from falling off during subsequent treatment or use, and maintains the long-term stability of the material.

[0021] Further, the concentration of the sodium hydroxide solution is 5wt%~10wt%. First, when the concentration of the sodium hydroxide solution is 5wt%~10wt%, its viscosity is close to the viscosity of water, then the interaction between sodium hydroxide and water in the solution is weak, and the solution fluidity is good. This low viscosity characteristic is conducive to the diffusion of copper ions in the solution. In the impregnation reaction, copper ions need to effectively diffuse into the fiber interior of the cotton fabric and react with the hydroxyl groups on the fiber. If the solution viscosity is too high, the diffusion rate of copper ions will be hindered, resulting in incomplete reaction or reduced reaction rate. Secondly, high-concentration sodium hydroxide solution (>10wt%) can cause the solution viscosity to increase sharply, because with the increase of solute concentration, the interaction between solute molecules is enhanced, forming more intermolecular hydrogen bonds and ionic bonds, thereby increasing the viscosity of the solution, and high-viscosity solution is not only unfavorable for the diffusion of copper ions, but also may affect the contact and wetting effect between the solution and the cotton fabric, further reducing the reaction efficiency. In addition, high-concentration sodium hydroxide solution may also bring other unfavorable factors. For example, it will increase the heat release during the reaction, causing the local temperature to be too high, affecting the stability and performance of the product. At the same time, high-concentration solutions may also cause corrosion or damage to equipment, increasing production costs and safety risks.

[0022] Further, the copper oxide or divalent copper salt is allowed to stand in the sodium hydroxide solution for 24 to 48 hours. First, through long-term standing, the copper oxide or divalent copper salt has enough time to fully react with the hydroxide ions in the sodium hydroxide solution to form stable sodium tetrahydroxycopperate. This long-term reaction can ensure sufficient contact and reaction between the reactants, thereby improving the purity and yield of the product. In addition, during the standing process, the solute and solvent in the solution will be fully mixed and diffused, which helps to form a uniform solution system. This uniformity is crucial for the subsequent impregnation reaction, and can ensure that the cotton fabric can uniformly absorb the copper ions in the solution during the impregnation process, thereby achieving a uniform modification effect. At the same time, during the standing process, the generated sodium tetrahydroxycopperate has enough time to rearrange and stabilize the molecules. This stabilization process helps to form a more stable and non-decomposable product, thereby improving the performance and service life of the final electromagnetic shielding material.

[0023] Further, in step S1, the cotton fabric is impregnated in a saturated NaOH solution of a divalent copper salt for 48 to 72 hours. First, the long impregnation reaction provides sufficient time for the chemical reaction between the cotton fabric fiber and the divalent copper salt, which helps the copper ions to fully penetrate into the cotton fiber and react with the hydroxyl groups on the fiber to form a stable coordination bond. This sufficient reaction ensures the uniform distribution and firm bonding of the copper ions on the cotton fiber. As the impregnation time increases, the coordination reaction between the copper ions and the cotton fiber is more thorough, and the coordination bond formed is more stable. At the same time, the hydrogen bonding between the hydroxyl groups in the cotton fiber molecules and the hydroxyl groups or water molecules in the tetrahydroxycopperate molecules is also enhanced. These interactions jointly improve the binding force between the copper ions and the cotton fibers, making the copper ions difficult to fall off during subsequent treatment. Finally, due to the uniform distribution and firm bonding of copper ions on cotton fibers, the prepared electromagnetic shielding material has better conductivity and electromagnetic shielding performance. Copper ions can quickly convert the electric field components in electromagnetic waves into current and conduct them through the interior of the material, thereby effectively attenuating the energy of the electromagnetic waves. In addition, the porous structure and conductivity of carbonaceous materials also scatter and absorb electromagnetic waves, further enhancing the electromagnetic shielding performance of the material.

[0024] Further, in step S2, the drying temperature is 50-70°C, and the drying time is 8-12h. First, the drying temperature of 50-70°C is moderate, which can effectively remove the excess water in the cotton fabric, and will not damage the structure of the cotton fiber due to excessive temperature. The moderate removal of water helps to reduce the deformation, shrinkage or color difference that may occur in the subsequent treatment. At the same time, drying at an appropriate temperature can ensure that the cotton fiber maintains its original shape and elasticity while removing water, and maintains its flexible characteristics, which helps to maintain the softness and feel of the cotton fabric, and is also conducive to the stable attachment of copper ions on the fiber. During the drying process, as the water evaporates, the pore structure on the surface of the cotton fiber may become clearer, which helps the copper ions to be better fixed on the fiber. At the same time, drying can also promote the further stabilization of the coordination bond formed between the copper ions and the fibers, and improve the adhesion and durability of the copper ions on the fibers. The drying time of 8-12 hours is relatively long, which can ensure that the water in the cotton fabric is fully removed, and long-term drying helps to reduce the residual water inside the cotton fabric and improve the drying effect.

[0025] Further, in step S2, high-temperature carbonization treatment is carried out under an argon atmosphere. First, during the high-temperature carbonization process, argon is used as a protective atmosphere to effectively isolate oxygen in the air, thereby preventing copper ions and fibers on the cotton fabric from undergoing oxidation reactions at high temperatures. Under an argon atmosphere, due to the absence of oxygen interference, the carbonization reaction can proceed more smoothly, which is conducive to the formation of a carbonaceous layer with a dense structure and stable performance. The carbonized cotton fabric contains a large amount of carbon elements, and its electrical conductivity will be significantly improved, and the high-temperature carbonization treatment under an argon atmosphere helps to form a more uniform and dense carbonaceous structure, thereby further improving the electrical conductivity of the material. The carbonized cotton fabric not only has electrical conductivity, but also has excellent electromagnetic shielding performance due to its porous structure and the characteristics of the carbonaceous material. The high-temperature carbonization treatment under an argon atmosphere helps to optimize the structure and performance of the carbonaceous material, so that it can better absorb, reflect and scatter electromagnetic waves, thereby improving the electromagnetic shielding effect of the material.

[0026] Further, in step S2, during the high-temperature carbonization treatment, the heating rate is 5°C / min, the holding temperature is 700-900°C, the holding time is 1-2h, the cooling rate is 2°C / min, and the temperature is cooled to 200°C and then naturally cooled to room temperature. The heating rate is 5°C / min. The slower heating rate helps to reduce the thermal stress caused by the rapid temperature change of the material during the heating process, which helps to prevent the cotton fabric from breaking or deforming due to excessive thermal stress at high temperature. The slower heating rate can also ensure that the cotton fabric is heated evenly during the entire heating process to avoid uneven performance or damage caused by local overheating. The holding temperature is 700-900°C, which is an ideal range for high-temperature carbonization treatment. At this temperature, the organic components in the cotton fabric can be fully pyrolyzed and carbonized to form a carbonaceous material with excellent electrical conductivity and electromagnetic shielding performance. The holding time of 1-2h can ensure that the organic components in the cotton fabric are fully carbonized to form a stable carbonaceous structure, which helps to improve the electrical conductivity and electromagnetic shielding performance of the material. A cooling rate of 2°C / min helps reduce the thermal stress caused by rapid temperature changes during the cooling process, which helps prevent the carbonized cotton fabric from breaking or deforming due to excessive thermal stress during the cooling process. A slower cooling rate also helps maintain the structural stability of the carbonized product and prevents performance degradation caused by rapid cooling. Natural cooling after cooling to 200°C can avoid internal stress or cracks caused by rapid cooling, which helps maintain the integrity and performance stability of the carbonized product. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0028] Figure 1 A schematic diagram of a process for preparing an electromagnetic shielding material in the present invention;

[0029] Figure 2 This is a bending diagram of the electromagnetic shielding material prepared in Example 1 of the present invention;

[0030] Figure 3 This is a SEM image of the electromagnetic shielding material prepared in Example 1 of the present invention;

[0031] Figure 4 This is the XRD pattern of the electromagnetic shielding material prepared in Example 1 of the present invention;

[0032] Figure 5This is a graph showing the variation of the electromagnetic shielding effectiveness of the electromagnetic shielding material prepared in Example 1 of the present invention with frequency;

[0033] Figure 6 This is a graph showing how the electromagnetic shielding effectiveness of the electromagnetic shielding material prepared in Example 3 of the present invention varies with frequency. DETAILED DESCRIPTION

[0034] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0035] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0036] Herein, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0037] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”

[0038] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0039] like Figure 1 As shown, the present invention provides a method for preparing an electromagnetic shielding material, comprising the following steps:

[0040] S1: placing cotton fabric in a saturated NaOH solution of a divalent copper salt, and immersing the cotton fabric for 48 to 72 hours to obtain a modified cotton fabric; specifically, placing the cotton fabric in a saturated NaOH solution of a divalent copper salt until the cotton fabric turns blue and the color does not change any more, and the blue attachment on the cotton fabric is sodium tetrahydroxycopperate;

[0041] The saturated NaOH solution of the divalent copper salt is prepared by placing copper oxide or a divalent copper salt in an excess sodium hydroxide solution and allowing it to react for 24 to 48 hours. Specifically, the copper oxide or a divalent copper salt can be placed in an excess sodium hydroxide solution and allowed to react until the solution turns blue and the color no longer changes, thereby obtaining a saturated NaOH solution of the divalent copper salt. In addition, the copper oxide here can be derived from the oxidation product on the surface of the metal copper wire.

[0042] The divalent copper salt may be copper sulfate or copper chloride. The concentration of the sodium hydroxide solution is 5wt% to 10wt%.

[0043] S2: After washing and drying the modified cotton fabric, carbonization treatment is performed under an argon atmosphere to obtain the electromagnetic shielding material. The drying temperature is 50-70°C and the drying time is 8-12 hours. During the carbonization treatment, the heating rate is 5°C / min, the insulation temperature is 700-900°C, the insulation time is 1-2 hours, the cooling rate is 2°C / min, and the temperature is cooled to 200°C and then naturally cooled to room temperature.

[0044] The invention obtains a light, flexible and good electromagnetic shielding material by impregnating cheap and easily available cotton cloth with copper and performing high-temperature carbonization treatment. The invention also has simple preparation process, strong operability, low cost, can be prepared in large quantities, and has broad development prospects.

[0045] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0046] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.

[0047] Example 1

[0048] A method for preparing an electromagnetic shielding material comprises the following steps:

[0049] (1) preparing 250 mL of sodium hydroxide solution, stirring with a magnetic stirrer until fully dissolved, wherein the sodium hydroxide accounts for 5 wt % of the sodium hydroxide solution;

[0050] (2) adding 10 g of metallic copper wire to a sodium hydroxide solution and allowing the solution to stand for 24 h until the solution turns blue and the color no longer changes, thereby obtaining a Cu(II) saturated NaOH solution;

[0051] (3) Immerse the cotton fabric in a sodium hydroxide solution for 48 hours until the cotton fabric turns blue and the color no longer changes;

[0052] (4) taking out the cotton fabric from the Cu(II) saturated NaOH solution and transferring it to a forced air drying oven for drying at 60°C for 8 h;

[0053] (5) The dried cotton fabric is transferred to a tubular furnace and heated to 700°C at a rate of 5°C / min under an argon atmosphere, and kept at this temperature for 1 h for high-temperature carbonization treatment. Thereafter, the temperature is decreased to 200°C at a rate of 2°C / min, and then naturally cooled to room temperature to obtain an electromagnetic shielding material.

[0054] Figure 2 This is a bending diagram of the electromagnetic shielding material prepared in Example 1 of the present invention. It can be seen from the figure that the electromagnetic shielding material prepared in the present invention has good flexibility, is resistant to bending and is not easily damaged.

[0055] Figure 3 This is a SEM image of the electromagnetic shielding material prepared in Example 1 of the present invention. It can be seen from the image that the metal copper particles are evenly deposited on the surface of the carbon fibers.

[0056] Figure 4 This is the XRD diagram of the electromagnetic shielding material prepared in Example 1 of the present invention. It can be seen from the figure that the material has three diffraction peaks at 43.3°, 50.4° and 74.1°. Through phase retrieval and comparison, it can be seen that these three diffraction peaks are all from pure copper (PDF No.851326), corresponding to the (111), (200) and (220) crystal planes, respectively. It can be determined that the surface of the prepared material is covered with copper.

[0057] Figure 5 This is a graph showing how the electromagnetic shielding effectiveness of the electromagnetic shielding material prepared in Example 1 of the present invention varies with frequency. It can be seen from the graph that within the frequency range of 8-12 GHz, the electromagnetic shielding effectiveness of the prepared electromagnetic shielding material is above 19 dB and averages 20 dB, which meets commercial requirements and has a relatively good electromagnetic shielding effect.

[0058] Example 2

[0059] A method for preparing an electromagnetic shielding material comprises the following steps:

[0060] (1) preparing 250 mL of sodium hydroxide solution, stirring with a magnetic stirrer until fully dissolved, wherein the sodium hydroxide accounts for 8 wt % of the sodium hydroxide solution;

[0061] (2) adding 10 g of metallic copper wire to a sodium hydroxide solution and allowing the solution to stand for 36 h until the solution turns blue and the color no longer changes, thereby obtaining a Cu(II) saturated NaOH solution;

[0062] (3) Immerse the cotton fabric in a sodium hydroxide solution for 60 hours until the cotton fabric turns blue and the color no longer changes;

[0063] (4) taking out the cotton fabric from the Cu(II) saturated NaOH solution and transferring it to a forced air drying oven for drying at 60°C for 10 h;

[0064] (5) The dried cotton fabric was transferred to a tubular furnace and heated to 800°C at a rate of 5°C / min under an argon atmosphere, and kept at this temperature for 1.5 h for high-temperature carbonization treatment. Thereafter, the temperature was decreased to 200°C at a rate of 2°C / min, and then naturally cooled to room temperature to obtain an electromagnetic shielding material.

[0065] Example 3

[0066] A method for preparing an electromagnetic shielding material comprises the following steps:

[0067] (1) preparing 250 mL of sodium hydroxide solution, stirring with a magnetic stirrer until fully dissolved, wherein the sodium hydroxide accounts for 10 wt % of the sodium hydroxide solution;

[0068] (2) adding 10 g of metallic copper wire to a sodium hydroxide solution and allowing the solution to stand for 48 h until the solution turns blue and the color no longer changes, thereby obtaining a Cu(II) saturated NaOH solution;

[0069] (3) Immerse the cotton fabric in a sodium hydroxide solution for 72 hours until the cotton fabric turns blue and the color no longer changes;

[0070] (4) taking out the cotton fabric from the Cu(II) saturated NaOH solution and transferring it to a forced air drying oven for drying at 60°C for 12 h;

[0071] (5) The dried cotton fabric is transferred to a tubular furnace and heated to 900°C at a rate of 5°C / min under an argon atmosphere, and kept at this temperature for 2 h for high-temperature carbonization treatment. Thereafter, the temperature is decreased to 200°C at a rate of 2°C / min, and then naturally cooled to room temperature to obtain an electromagnetic shielding material.

[0072] Figure 6 This is a graph showing how the electromagnetic shielding effectiveness of the electromagnetic shielding material prepared in Example 3 of the present invention varies with frequency. It can be seen from the graph that within the frequency range of 8-12 GHz, the electromagnetic shielding effectiveness of the prepared electromagnetic shielding material is above 27 dB, has a good electromagnetic shielding effect, and can shield more than 99% of electromagnetic waves.

[0073] Example 4

[0074] A method for preparing an electromagnetic shielding material comprises the following steps:

[0075] S1: placing copper oxide in an excess of 5wt% sodium hydroxide solution and allowing it to react for 48 hours until the solution turns blue and the color no longer changes, thereby obtaining a saturated NaOH solution of a divalent copper salt; placing cotton fabric in the saturated NaOH solution of a divalent copper salt and immersing it for 48 hours to obtain a modified cotton fabric;

[0076] S2: After washing the modified cotton fabric with water, drying it at 50°C for 12 hours, and carbonizing it in an argon atmosphere to obtain the electromagnetic shielding material. During the carbonization process, the heating rate is 5°C / min, the holding temperature is 700°C, the holding time is 2 hours, the cooling rate is 2°C / min, and the temperature is cooled to 200°C and then naturally cooled to room temperature.

[0077] Example 5

[0078] A method for preparing an electromagnetic shielding material comprises the following steps:

[0079] S1: placing copper sulfate in an excess of 10wt% sodium hydroxide solution and allowing it to react for 24 hours until the solution turns blue and the color no longer changes, thereby obtaining a saturated NaOH solution of a divalent copper salt; placing cotton fabric in the saturated NaOH solution of a divalent copper salt and immersing it for 72 hours to obtain a modified cotton fabric;

[0080] S2: After washing the modified cotton fabric with water, drying it at 70°C for 8 hours, and carbonizing it in an argon atmosphere to obtain the electromagnetic shielding material. During the carbonization process, the heating rate is 5°C / min, the holding temperature is 900°C, the holding time is 1 hour, the cooling rate is 2°C / min, and the temperature is cooled to 200°C and then naturally cooled to room temperature.

[0081] Example 6

[0082] A method for preparing an electromagnetic shielding material comprises the following steps:

[0083] S1: placing cupric chloride in an excess of 8wt% sodium hydroxide solution and allowing it to react for 30 hours until the solution turns blue and the color no longer changes, thereby obtaining a saturated NaOH solution of a divalent copper salt; placing cotton fabric in the saturated NaOH solution of a divalent copper salt and immersing it for 50 hours to obtain a modified cotton fabric;

[0084] S2: After washing the modified cotton fabric with water, drying it at 60°C for 10 hours, and carbonizing it in an argon atmosphere to obtain the electromagnetic shielding material. During the carbonization process, the heating rate is 5°C / min, the holding temperature is 800°C, the holding time is 1.5 hours, the cooling rate is 2°C / min, and the temperature is cooled to 200°C and then naturally cooled to room temperature.

[0085] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

[0086] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing an electromagnetic shielding material, characterized in that: The following steps are involved: S1: placing cotton fabric in a saturated NaOH solution of divalent copper salt for immersion reaction to obtain modified cotton fabric; S2: After washing and drying the modified cotton fabric, carbonization treatment is performed to obtain the electromagnetic shielding material.

2. The method for preparing an electromagnetic shielding material according to claim 1, characterized in that: The saturated NaOH solution of the divalent copper salt is prepared by placing copper oxide or divalent copper salt in an excess of sodium hydroxide solution and allowing to react.

3. The method for preparing an electromagnetic shielding material according to claim 2, characterized in that: The concentration of the sodium hydroxide solution is 5wt% to 10wt%.

4. The method for preparing an electromagnetic shielding material according to claim 2, characterized in that: The copper oxide or divalent copper salt is allowed to stand in a sodium hydroxide solution to react for 24 to 48 hours.

5. The method for preparing an electromagnetic shielding material according to claim 1, characterized in that: In step S1, the cotton fabric is immersed in a saturated NaOH solution of a divalent copper salt for 48 to 72 hours.

6. The method for preparing an electromagnetic shielding material according to claim 1, characterized in that: In step S2, the drying temperature is 50-70°C and the drying time is 8-12 hours.

7. The method for preparing an electromagnetic shielding material according to claim 1, characterized in that: In step S2, a carbonization treatment is performed in an argon atmosphere.

8. The method for preparing an electromagnetic shielding material according to claim 1, characterized in that: In step S2, during the carbonization treatment, the heating rate is 5°C / min, the holding temperature is 700-900°C, the holding time is 1-2h, the cooling rate is 2°C / min, and the temperature is cooled to 200°C and then naturally cooled to room temperature.

9. An electromagnetic shielding material, characterized in that: It is prepared by the method according to any one of claims 1 to 8.

10. Use of the electromagnetic shielding material described in claim 9 in electronic equipment.